Characterization of the set of equilibria in max-min group contests with continuous efforts and a private good prize - Gilli, Mario,Sorrentino, Andrea (Fondazione Eni Enrico Mattei, 2024)
We characterise the set of equilibria in a deterministic group contest with the weakest-link impact function, continuous efforts and a private good prize, complementing the results obtained by Chowdhury et al. (2016). We consider a two-stages two-groups model, where in the first stage the agents simultaneously choose the sharing rule, while in the second stage they choose efforts. Despite the existence of within-group symmetric Nash equilibria in pure strategies in the effort stage, there are combinations of possible sharing rules such that no pure strategy effort equilibria exist, hence for these sharing rules, the continuation payoffs are not defined, so that there exist no subgame perfect Nash equilibria in pure stragies. However, limiting ourselves to the restricted sharing rules case, we are able to state that there are continua of subgame perfect equilibria. In this case, by additional restrictions on the effort levels of each class of effort equilibria, we are able to computationally characterise the set of subgame perfect equilibria in pure strategies.
10419/301108
Keywords: Graue Literatur; Group contests; sharing rules; indeterminacy